Adaptive physical activity as an incentive for maintaining interest in a healthy lifestyle in the elderly (60-64 years old) and the key to longevity - Evseeva O.E.; Ladygina E.B.; Evseev S.P.; Aksenov A.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is the theoretical substantiation of recommendations on the use of adaptive physical culture (AFC) to stimulate the desire for an active life in the elderly (60-64 years) in people with sensory, motor and cognitive disabilities. Methods and structure of the study. As part of the implementation of the state task for 2024 on research work devoted to the development of scientifically sound recommendations for increasing motivation for active longevity by means of ROS among older citizens (taking into account sensory, motor and mental disorders), an analysis of existing scientific publications on this topic was carried out, as well as monitoring of the level of motivation to active longevity in people aged 60 years and older. Results and conclusions. The results of the analysis and monitoring made it possible to identify key strategies that contribute to creating favorable conditions for the formation of motivation for active longevity through ROS. The first strategy is to study and take into account the individual values and life goals of each person. The second is to ensure positive emotions from physical activity and to use the principles of successful aging. The third is to take into account the peculiarities of diseases and contraindications in the organization of physical activity for the elderly. It is proposed to apply the developed approaches to motivation formation within the framework of complex interaction of specialists working with the elderly in the fields of healthcare, physical education, social protection and others.